Visual mapping for natural gas pipe inspection. (April 2015) - Hansen, Peter; Alismail, Hatem; Rander, Peter; Browning, Brett
Validating the integrity of pipes is an important task for safe natural gas production and many other operations (e.g. refineries, sewers, etc.). Indeed, there is a growing industry of actuated, actively driven mobile robots that are used to inspect pipes. Many rely on a remote operator to inspect data from a fisheye camera to perform manual inspection and provide no localization or mapping capability. In this work, we introduce a visual odometry-based system using calibrated fisheye imagery and sparse structured lighting to produce high-resolution 3D textured surface models of the inner pipe wall. Our work extends state-of-the-art visual odometry and mapping for fisheye systems to incorporate weak geometric constraints based on prior knowledge of the pipe components into a sparse bundle adjustment framework. These constraints prove essential for obtaining high-accuracy solutions given the limited spatial resolution of the fisheye system and challenging raw imagery. We show that sub-millimeter resolution modeling is viable even in pipes which are 400 mm (16") in diameter, and that sparse range measurements from a structured lighting solution can be used to avoid the inevitable monocular scale drift. Our results show that practical, high-accuracy pipe mapping from a single fisheye camera is within reach.